Brain magnetic resonance imaging examination in a patient with non‐magnetic resonance conditional pacemaker. Issue 5 (13th May 2017) - Nakai, Toshiko; Sato, Toshiaki; Soejima, Kyoko; Takamine, Yusuke; Watanabe, Mitsuru; Kobayashi, Kazutaka; Oshima, Hideki; Fukaya, Chikashi; Okumura, Yasuo; Ohkubo, Kimie; Kunimoto, Satoshi; Watanabe, Ichiro; et al.
Abstract: Clinical dilemmas arise when patients with a non‐magnetic resonance (MR) conditional pacemaker are required to undergo magnetic resonance imaging (MRI). We encountered a pacemaker patient with debilitating non‐motor symptoms of Parkinson׳s disease, who required an MRI prior to deep brain stimulation (DBS) surgery. MRI was performed safely without adverse events despite the presence of a conventional pacemaker.